The Effect of Dispatch Methods on a Recruiting Campaign for a Business Survey: Evidence from Germany - Przemyslaw Brandt; Katrin Demmelhuber; Klaus Wohlrabe (Center for Economic Studies and Ifo Institute (CESifo), 2020)
The ifo Institute for Economic Research has been conducting the ifo business survey since its foundation in 1949. To ensure stability of participation rates, regular sample recruitment is indispensable. Does the dispatch method matter for response rates of a recruiting campaign? To answer this question, we conducted a controlled experiment involving invitation letters sent out to over 8,000 German industrial firms in May 2019. Our results show that standard mailing significantly increases the response rate compared to “Dialogpost” (bulk mail). From a cost perspective, costs for standard mailing outweigh this effect.
Keywords: C83; C93; 330; business survey; recruitment; response rate; postage; bulk mail; envelope